The influence of intellectual capital on the performance of Telekom Malaysia - Ismail, Mazlan (2005)
This case study investigates the influence of intellectual capital on the performance of Telekom Malaysia. It consists of investigating the level of intellectual capital, the effect and influence of spiritual capital, the importance of knowledge management and managing and leveraging of intellectual capital on the performance. A mixed method research approach is used with strategies of inquiry that involve sequential quantitative and qualitative data collection. With broad intellectual capital theoretical perspective guides including the spiritual capital, the data collection is done sequentially in phases beginning with a questionnaires survey, followed by secondary data analysis and finally the interview sessions. Independent variables are human capital, structural capital, relational capital, spiritual capital, knowledge management and managing and leveraging of intellectual capital and dependent variable is performance improvement in the aspect of organisational and business leadership, operating efficiency and business performances. The survey involves the executives to assistant general manager levels working at various departments at the 14 states business areas and headquarters level and the interviewees are from the general manager to senior vice-president and CEO. Statistical techniques such as means of variance, factor analysis, ANOVA test, regression analysis, path analysis and narrative passages are used in analysing the data. The study indicates a positive significant relationship between relational, human, spiritual and structural capital and managing and leveraging of intellectual capital on the performance whereas knowledge management has indirect relationship to the performance. This research makes important theoretical and empirical contributions to the literature on the influence of intellectual capital, on the effect and influence of spiritual capital and the importance of managing and leveraging of intellectual capital on the performance of the organisation. By having a stronger spiritual capital within the higher management to manage and leverage the present intellectual capital, Telekom Malaysia will achieve further performance improvement in the future